Keterwakilan Perempuan di Birokrasi: Fenomena Glass Ceilling Pada Kementerian Republik Indonesia - Aisyah; Almirah Ghaisani Putri; Yulia Sri Kanti; Aniqotul Ummah (Jurnal Studi Gender dan Anak, 2024)
As time progresses, the involvement of women becomes significantly apparent in various aspects of life such as education, healthcare, economy, and politics, as well as being crucial within bureaucracy. Despite the importance of women's involvement in bureaucracy, there still exists gender inequality particularly in occupying certain positions. The phenomenon known as the glass ceiling inhibits the career advancement of female workers. In Indonesia, this glass ceiling phenomenon is further reinforced by the patriarchal culture, making it difficult for women working in government ministries to attain promotions or higher positions. Research conducted using qualitative methods, employing books, journals, articles, and other sources as data, indicates that in Indonesia, there are still several obstacles hindering women from advancing in their careers. These obstacles include a lack of awareness and understanding about the importance of gender equality among leaders within the ministry environment. Data also indicates a very low representation of women in crucial positions within Indonesian ministries. However, there are several ways to address the glass ceiling phenomenon, such as setting examples for society that women can be leaders, empowering female employees, and providing skill training to instill knowledge and confidence for them to become leaders. Keywords: Glass Ceiling, Feminism, Position